2015
DOI: 10.1080/02687038.2015.1070950
|View full text |Cite
|
Sign up to set email alerts
|

Luria’s classification of aphasias and its theoretical basis

Abstract: Background: Every qualified neuropsychologist knows about Luria's contribution to neuropsychology and aphasiology in general, but many of them believe his ideas to be out of date. Aims: The purpose of this article is to investigate Alexander Luria's methodology of classification of aphasias and to describe the forms of aphasias that he distinguished.Main contribution: The article shows that the classification of aphasias was based on a profound theoretical research performed by Luria together with the founder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 38 publications
1
35
0
5
Order By: Relevance
“…However, in the study by Tsvetkova, patients with acoustic-amnestic and semantic types of aphasia (predominantly of vascular etiology) were not divided. The later studies of semantic deficits, which distinguished both of these aphasic forms and slight visual agnosia [19][20][21], confirmed Luria's earlier viewpoint [1,2]. Special experiments showed that patients with semantic aphasia, along with poor understanding of reversible grammatical constructions, experienced nominative problems because of the poor operating with a word's categorical meaning.…”
Section: Introductionsupporting
confidence: 55%
“…However, in the study by Tsvetkova, patients with acoustic-amnestic and semantic types of aphasia (predominantly of vascular etiology) were not divided. The later studies of semantic deficits, which distinguished both of these aphasic forms and slight visual agnosia [19][20][21], confirmed Luria's earlier viewpoint [1,2]. Special experiments showed that patients with semantic aphasia, along with poor understanding of reversible grammatical constructions, experienced nominative problems because of the poor operating with a word's categorical meaning.…”
Section: Introductionsupporting
confidence: 55%
“…Acoustic-mnestic aphasia is characterized by instability of auditory images of words which can lead to the alienation of word meaning. Sensory aphasia is characterized by impaired comprehension based on the primary impairment of phonemic perception (Akhutina, 2016;Luria, 1970). Both our patients complied with this view, at the same time extending the notion of the syndromes into the domain of verb and sentence processing.…”
Section: Discussionmentioning
confidence: 99%
“…The types of aphasia of the brain-damaged speakers were established using Luria's classification (Akhutina, 2015;. The four aphasia types present in the corpus include two with non-fluent speech output (efferent motor and dynamic aphasias) and two with fluent speech output (sensory and acoustic-mnestic aphasias).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semantic aphasia -a type of aphasia not included in the Boston classification -results from a lesion in the area of the left temporalparietal-occipital junction (Akhutina 2015;Dragoy et al 2015). Two specific deficits underlying semantic aphasia are difficulties in: (i) finding words and (ii) understanding logical-grammatical constructions such as genitive, passive, double negation or embedded clause.…”
Section: Introductionmentioning
confidence: 99%